Lifelong learning policy making process in Turkey: the lifelong learning coordination law - Seçkin, Onur. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2015., 2015)
The aim of this study is to explore lifelong learning (LLL) policy making process in Turkey under the global effect in the case of the Lifelong Learning Coordination Law (HBÖKK). Findings emerged as a result of a content analysis of in-depth elite interviews with major policy makers in the HBÖKK making process with the assistance of Qualitative and Mixed Methods Data Analyses Software, MAXQDA. The findings indicate that bringing the LLL concept and the HBÖKK into the policy agenda in Turkey is mostly related to global changes and the accession process of Turkey to the European Union. Maintaining the coordination of LLL activities, increasing participation rate in LLL were the other reasons for bringing the HBÖKK into the policy agenda of Turkey. The findings showed that having operations and activities in the field of LLL, particularly on vocational education and training, was the main criteria for the selection of stakeholders in the HBÖKK making process. The stakeholders mostly take the LLL issue into hand in terms of vocational education and training. There were conflicts in the process among the stakeholders especially related to the issue of financing of LLL and changing authorities that will emerge as a result of the HBÖKK. There were some problems related to the participative dimension of the policy making process. Besides, the process was affected negatively due to administrative changes.
Keywords: Continuing education.; Continuing education -- Turkey.